Pengaruh Model Pembelajaran Flipped Classroom terhadap Keaktifan Siswa pada Mata Pelajaran Akidah Akhlak Kelas X di MAN 1 Bogor - Tazkiyani, Intan Audia; Lisnawati, Santi; Hakiem, Hilman (Lembaga Yasin AlSys, 2025)
This study aims to determine the effect of the Flipped Classroom learning model on student engagement in the subject of Akidah Akhlak in class X at MAN 1 Bogor. This research is motivated by the low student engagement in the subject of Akidah Akhlak due to the insufficient use of conventional methods that do not actively involve students in the learning process, which has a significant impact on the context of the research. The objective of this study is to measure the extent of the influence of the Flipped Classroom learning model on student engagement in the learning process. The method used is quantitative with a quasi-experimental research design of a non-equivalent control group design, involving a sample of 70 students selected using non-probability sampling with purposive sampling techniques. The results of the study indicate that the Flipped Classroom model has a positive effect on student engagement in the subject of Akidah Akhlak in class X at MAN 1 Bogor. The better the learning model and methods used by the teacher, the higher the student engagement in the learning process. Therefore, if a teacher designs the learning process well using various models and methods, it will have a positive impact on student engagement in learning.